Development and validation of UV spectrophotometric method for quantitative estimation of Promethazine HCl in phosphate buffer saline pH 7.4 - Nurahmanto, Dwi (International Current Pharmaceutical Journal, 2013)
A new, sensitive, rapid, simple, specific and economical procedure has been developed for determination Promethazine HCl in phosphate buffer saline pH 7.4. The purpose of this analytical validation procedure is to determine a process of assessment and to validate it by laboratory experiments to prove that the method meets the minimum standard for laboratory use. This analytical method for the determination of Promethazine HCl in phosphate buffer saline pH 7.4 can be used to estimate the amount of promethazine HCl penetrated and dissolved in the blood vessels in vitro by penetration study. The method is based on the ultraviolet light absorbance at 251 nm which is the maximum wavelength of the concerned drug. This method can be succesfully applied for determination of drug in phosphate buffer saline pH 7.4 . The results of the analysis have been validated statistically and by recovery studies. DOI: http://dx.doi.org/10.3329/icpj.v2i8.15589 International Current Pharmaceutical Journal, July 2013, 2(8): 141-142